Coarse stone tools (Scottish Historical and Archaeological Internet Reports, 2004)
Seven stone tools were recovered. They comprised four flakes probably relating to breakage of hammerstones and other cobble tools, a bevelled pebble and two fragments of beach cobbles, one of which was probably used as a pot boiler.